Foot and ankle trauma management during the COVID-19 pandemic: Experiences from a major trauma unit - Shah, Rohi (J Clin Orthop Trauma, 2021)
The COVID-19 pandemic has resulted in a paradigm shift in clinical practice, particularly in ways in which healthcare is accessed by patients and delivered by healthcare practitioners. Many of these changes have been serially modified in adaptation to growing service demands and department provision capacity. We evaluated the impact of the pandemic on the foot and ankle service at our trauma unit, assessing whether these adaptations to practice were justifiable, successful and sustainable for the future. This was a single-centre, retrospective cohort study analysing the patient care pathway from admission to discharge, for two pre-defined timeframes: Phase 0 (pre-lockdown phase) and Phase 1 (lockdown phase). Patients were split into stable and unstable injuries depending on their fracture pattern. The follow-up modality and duration were evaluated. Trauma throughput for the equivalent timeframe in 2019 was also analysed for comparison. There were 106 unstable fractures and 100 stable fractures in 2020.78 interventional procedures were performed on 72 patients with unstable fractures in Phase-1. Close contact casting was performed on 13 patients at presentation in the ED. Selective patients underwent partial fixation in theatre, which still provided adequate stability. 35% of patients with a stable fracture were discharged directly from the ED with written advice from a review letter. The treatment modality in selective patients, particularly the vulnerable should be carefully assessed. Interventions performed at presentation often negate the need for admission. Partial fixation reduces intraoperative time and surgical insult. Integrating telemedicine into the care pathway, particularly for stable ankle fractures reduces the need for physician-patient contact and eases follow-up burden. Many of our recommended changes are easily replicated in other clinical settings. Should these adaptations demonstrate long-term sustainability, it is likely they will remain incorporated into future clinical practice.